Wireless Algorithms, Systems, and Applications 8th International Conference, WASA 2013, Zhangjiajie, China, August 7-10,2013, Proceedings - Ren, Kui; Liu, Xue; Liang, Weifa; Xu, Ming; Jia, Xiaohua; XING, KAI (Theoretical Computer Science and General Issues,, 2013)
This book constitutes the refereed proceedings of the 7th International Conference on Wireless Algorithms, Systems, and Applications, WASA 2013, held in Zhangjiajie, China, in August 2013. The 25 revised full papers presented together with 18 invited papers were carefully reviewed and selected from 80 submissions. The papers cover the following topics: effective and efficient state-of-the-art algorithm design and analysis, reliable and secure system development and implementations, experimental study and testbed validation, and new application exploration in wireless networks.